2008
DOI: 10.1109/tps.2008.923745
|View full text |Cite
|
Sign up to set email alerts
|

Reflection of Solitons at Critical Density of Negative Ions: Contribution of Thermal and Gyratory Motions of Ions

Abstract: On the basis of appropriate modified KortewegdeVries (mKdV) equation derived for three cases of n n0 < n e0 , n n0 = n e0 , and n n0 > n e0 together with n n0 (n e0 ) as the density of negative ions (electrons), we observe that compressive and rarefactive mKdV solitons propagate in an inhomogeneous magnetized plasma having negative ions at their critical density. Two types of modes (fast and slow) separately evolve as the compressive and rarefactive solitons. However, only the solitons corresponding to the fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…However, the terms without sech 2 represent the shift of this structure. Consistent to the observation of earlier work [35], the soliton is found to be shifted after its reflection, and the shift amounts of the first two terms of RHS of Eq. (47), i.e.,…”
Section: Reflection Of Solitary Structuressupporting
confidence: 89%
See 1 more Smart Citation
“…However, the terms without sech 2 represent the shift of this structure. Consistent to the observation of earlier work [35], the soliton is found to be shifted after its reflection, and the shift amounts of the first two terms of RHS of Eq. (47), i.e.,…”
Section: Reflection Of Solitary Structuressupporting
confidence: 89%
“…The occurrence of only the compressive solitons in the present plasma can be understood as follows. In negative ion containing plasmas, there exists a critical density of negative ions below which compressive solitons exist and above which rarefactive solitons propagate [34,35]. Since in the present plasma having negatively charged stationary dust grains there does not exist such critical density neither a and a R vanish nor carry negative values, only the compressive solitons are found to evolve.…”
Section: Solitary Structuresmentioning
confidence: 66%
“…For this reason, lesser is the amount of energy of the incident soliton and hence, smaller is the amount of energy that is being used in shifting the soliton. Malik et al [31] had also observed that when the incident soliton is reflected strongly then the amplitude of reflected soliton and the reflection coefficient attain higher values. However, the shift was found to behave oppositely [31].…”
Section: Soliton Reflection: Soliton Shift and Reflection Conditionmentioning
confidence: 97%
“…Malik et al [31] had also observed that when the incident soliton is reflected strongly then the amplitude of reflected soliton and the reflection coefficient attain higher values. However, the shift was found to behave oppositely [31]. In contrast to this, in the presence of ionization, the shift and reflection coefficients are found to behave consistently.…”
Section: Soliton Reflection: Soliton Shift and Reflection Conditionmentioning
confidence: 97%
See 1 more Smart Citation